Examining Faculty Perception of Their Readiness to Teach Online - Ma; Budhrani, Kiran; Wang, Chuang (Online learning (Newburyport, Mass.), 2019)
Faculty readiness to teach online is a state of faculty preparedness for online teaching. In this study, it is measured by faculty attitudes about the importance of online teaching competencies and faculty's perceptions of their ability to confidently teach online. Validity and reliability of faculty responses to an online instrument and factors related to faculty perception are examined. Descriptive statistics and item-level means for the competencies are provided. For course design, course communication, and technical competencies, faculty rated the perception of importance higher than they rated their ability in these areas, whereas for time management their perception of their ability was higher than their attitude about its importance. MANOVA showed significant differences in gender, years of teaching online, and delivery method for faculty perceptions of importance of online teaching competencies. Significant differences were also noted in years of teaching online and delivery method with respect to ability to teach online. Keywords: faculty readiness, online teaching, faculty attitude, faculty ability, faculty perception